Analysis Of Swallow's Nest Tax Collection Supervision In The City Of Parepare - Burhan; Muh. Hariansyah; Muh. Rifqi; Amira Isnaen; Nurhaliza; Andi Nurwanah (Journal AK-99, 2023)
This study aims to look at the process of collecting swallow's nests in Parepare City based on Regional Regulation of Parepare City No. 1 of 2014 concerning Tax on Swallow's Nests. And to see how the collection of swallow's nest tax in Parepare City is in accordance with Regional Regulation No. 1 of 2014 concerning Swallow's Nest Tax. Data techniques used in this study were interviews, observation and documentation. The information in this study is the head of the midwife and education staff. The data analysis technique used in this research is qualitative analysis. The swallow's nest tax collection system used by the City Government of Parepare is Self Assessment, in which taxpayers are given in order to report, calculate and pay taxes owed but the implementation of tax collection in Parepare City has not been running because of the awareness of taxpayers in reporting their taxes, calculating, and pay for it. Based on the results of the field assessment research, it shows that the potential of the buildings identified as providers of swiftlet nesting sites has spread across four sub-districts, namely Soreang, Ujung, Bacukiki and West Bacukiki. This distribution shows that the potential for swallow's nest tax revenue is quite high. This can be seen from the development of the Swiftlet's Nest taxpayer (WP) in 2015, only 20 WP, but in 2018 it has reached 70 WP, then in 2019 there are 82 WP and in 2020, there are 86 WP, so it can be concluded that from 2018 -2020 the number of taxpayers has increased.